Usprawnianie komunikacji słownej w wybranych wariantach choroby Alzheimera: typowym i językowym - Domagała, Aneta; Sitek, Emilia J. (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2022)
<span dir="ltr" style="left: calc(var(--scale-factor)*74.66px); top: calc(var(--scale-factor)*482.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00715);" role="presentation">The paper reviews the methods for improving verbal communication <span dir="ltr" style="left: calc(var(--scale-factor)*354.57px); top: calc(var(--scale-factor)*482.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.994879);" role="presentation">in selected vari<span dir="ltr" style="left: calc(var(--scale-factor)*75.34px); top: calc(var(--scale-factor)*496.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.988892);" role="presentation">ants of Alzheimer’s <span dir="ltr" style="left: calc(var(--scale-factor)*156.20px); top: calc(var(--scale-factor)*496.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.03099);" role="presentation">disease, both in the typical and language variant. It emphasises <span dir="ltr" style="left: calc(var(--scale-factor)*75.21px); top: calc(var(--scale-factor)*510.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.04647);" role="presentation">the need to <span dir="ltr" style="left: calc(var(--scale-factor)*124.05px); top: calc(var(--scale-factor)*510.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.02382);" role="presentation">optimise the management within the framework of patient<span dir="ltr" style="left: calc(var(--scale-factor)*362.06px); top: calc(var(--scale-factor)*510.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.0176);" role="presentation">centred care, <span dir="ltr" style="left: calc(var(--scale-factor)*75.34px); top: calc(var(--scale-factor)*524.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00011);" role="presentation">allowing to <span dir="ltr" style="left: calc(var(--scale-factor)*123.62px); top: calc(var(--scale-factor)*524.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.02194);" role="presentation">address individual needs. As far as indirect interventions are concerned, <span dir="ltr" style="left: calc(var(--scale-factor)*75.21px); top: calc(var(--scale-factor)*538.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01767);" role="presentation">the article presents techniques aimed at improving communication <span dir="ltr" style="left: calc(var(--scale-factor)*348.39px); top: calc(var(--scale-factor)*538.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00028);" role="presentation">with the affected <span dir="ltr" style="left: calc(var(--scale-factor)*75.32px); top: calc(var(--scale-factor)*552.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.0086);" role="presentation">person, and more broadly <span dir="ltr" style="left: calc(var(--scale-factor)*180.61px); top: calc(var(--scale-factor)*552.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00036);" role="presentation">– aimed at preserving the quality <span dir="ltr" style="left: calc(var(--scale-factor)*314.25px); top: calc(var(--scale-factor)*552.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.978502);" role="presentation">of life in the course of the <span dir="ltr" style="left: calc(var(--scale-factor)*75.18px); top: calc(var(--scale-factor)*566.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01136);" role="presentation">illness. Among direct interventions, those aimed at selected system abilities and sup<span dir="ltr" style="left: calc(var(--scale-factor)*75.32px); top: calc(var(--scale-factor)*580.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00016);" role="presentation">porting language function <span dir="ltr" style="left: calc(var(--scale-factor)*180.46px); top: calc(var(--scale-factor)*580.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.97832);" role="presentation">in the context of cognitive and social function <span dir="ltr" style="left: calc(var(--scale-factor)*361.88px); top: calc(var(--scale-factor)*580.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.996402);" role="presentation">are presented. <span dir="ltr" style="left: calc(var(--scale-factor)*74.92px); top: calc(var(--scale-factor)*594.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.966049);" role="presentation">It is shown how speech and language therapy can integrate <span dir="ltr" style="left: calc(var(--scale-factor)*303.94px); top: calc(var(--scale-factor)*594.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.993336);" role="presentation">other therapeutic paradigms, <span dir="ltr" style="left: calc(var(--scale-factor)*66.36px); top: calc(var(--scale-factor)*62.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.995325);" role="presentation">developed in psychology, such as patient<span dir="ltr" style="left: calc(var(--scale-factor)*228.81px); top: calc(var(--scale-factor)*62.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00916);" role="presentation">centred therapy and cognitive neuropsycho<span dir="ltr" style="left: calc(var(--scale-factor)*66.28px); top: calc(var(--scale-factor)*76.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.991689);" role="presentation">logical rehabilitation.